PENGARUH INFLASI, BI RATE, SUKU BUNGA KREDIT UMKM TERHADAP NON PERFORMING LOAN KREDIT UMKM PADA BANK UMUM - Suharna Suharna (Jurnal Ilmiah Akuntansi Universitas Pamulang, 2020)
This study aims to obtain empirical evidence on the influence of inflation, rate of Bank Indonesia, and credit interest rate on non - performing SMEs credit loan at Commercial Banks. This study uses secondary data obtained from quarterly OJK reports and Bank Indonesia monthly reports for the period of 2014 - 2018. Multiple linear regression models are used to test the hypotheses of this study. It was found that the inflation rate and the rate of Bank Indonesia individually doesn't have a siignificant influence on non - performing SMEs credit loans. On the other hand, it was found that credit interest rate has a signifinicant influence on non - performing SMEs credit loans.